2012
DOI: 10.1121/1.4725963
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal directivity of low- and high-frequency energy in speech and singing

Abstract: Speech and singing directivity in the horizontal plane was examined using simultaneous multi-channel full-bandwidth recordings to investigate directivity of high-frequency energy, in particular. This method allowed not only for accurate analysis of running speech using the long-term average spectrum, but also for examination of directivity of separate transient phonemes. Several vocal production factors that could affect directivity were examined. Directivity differences were not found between modes of product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 16 publications
(19 reference statements)
4
34
1
1
Order By: Relevance
“…Concerning the radiated sound field, the presence of higher order modes is a plausible explanation for directivity effects at high frequency (Monson et al, 2012) which cannot be explained by plane wave theory. The present study will be extended to the case of fricative sounds for which, due to the wide-band spectrum of the turbulent source as well as its location, higher order modes are expected not only to be essential in terms of propagation and radiation, but also in terms of aeroacoustic interaction with the sound generation (Hirschberg et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Concerning the radiated sound field, the presence of higher order modes is a plausible explanation for directivity effects at high frequency (Monson et al, 2012) which cannot be explained by plane wave theory. The present study will be extended to the case of fricative sounds for which, due to the wide-band spectrum of the turbulent source as well as its location, higher order modes are expected not only to be essential in terms of propagation and radiation, but also in terms of aeroacoustic interaction with the sound generation (Hirschberg et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Moore et al (2008) attributes these higher band levels to noise from the microphone used in the earlier study, but it is possible that microphone placement or the recording material itself caused the differences in HFE, leading to these disparities (e.g., an increase in the number of voiceless fricatives would potentially lead to increased HFE band levels in the LTAS). The SPLs reported here were verified by multiple Type 1 precision microphones recording simultaneously in the anechoic chamber (Monson et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…(A distance of 60 cm was used here due to space constraints in the anechoic chamber; see Monson et al, 2012) True mean levels reported here were calculated by converting dB levels to linear squared-pressure amplitudes, taking the mean, and converting this value back to dB. None of the signals were "pre-emphasized" in this study, thus the levels reported represent actual HFE levels of the raw singing/speech signal.…”
Section: Acoustical Analysismentioning
confidence: 99%
“…However, average performance on stop consonant categorization (50.6%) was nearly as good as average accuracy for the fricatives (59.7%). One might also predict greater performance using HFE for female speech given that female speech tends to have greater HFE overall (Monson et al, 2012a). Whereas accuracy was greater for female-produced tokens, these differences were relatively modest (3 percentage points for vowels and 4 percentage points for consonants).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the low-frequency masker was to ensure that listeners were using HFE, per se, and not distortion products that may be present in the lower frequencies. The HFE amplitude was set to 47 dB root-mean-square sound pressure level (SPL rms ) and the low-frequency masker was set to 62 dB SPL rms , which are typical levels produced during normal speech for a speaker facing the listener (Monson et al, 2012a(Monson et al, , 2012b.…”
Section: Stimulimentioning
confidence: 99%